2021
DOI: 10.1371/journal.pbio.3001041
|View full text |Cite
|
Sign up to set email alerts
|

The E3 ubiquitin ligase Cul4b promotes CD4+ T cell expansion by aiding the repair of damaged DNA

Abstract: The capacity for T cells to become activated and clonally expand during pathogen invasion is pivotal for protective immunity. Our understanding of how T cell receptor (TCR) signaling prepares cells for this rapid expansion remains limited. Here we provide evidence that the E3 ubiquitin ligase Cullin-4b (Cul4b) regulates this process. The abundance of total and neddylated Cul4b increased following TCR stimulation. Disruption of Cul4b resulted in impaired proliferation and survival of activated T cells. Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 96 publications
(122 reference statements)
4
13
0
Order By: Relevance
“…These findings are consistent with a very recent report that ablation of Cul4b in mature T cells resulted in impaired survival and proliferation accompanied by accumulation of DNA damage upon T-cell stimulation (39). This recent study further demonstrated that Cul4-Ddb1-DCAF1 E3 ligase complex associated with a DNA damage repair complex including SMC1A and promoted phosphorylation of Smc1a to aid in DNA damage repair (39). As Ddb1 is crucial for activity of Cul4-Ddb1-DCAFs E3 ligase complex, deletion of Ddb1 in effector CD4 + T cells could result in augmented protein levels of substrates involved in regulation of cell cycle, such as Cdt1 (18,19), p21 (20,21), and Cyclin D (40)(41)(42).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings are consistent with a very recent report that ablation of Cul4b in mature T cells resulted in impaired survival and proliferation accompanied by accumulation of DNA damage upon T-cell stimulation (39). This recent study further demonstrated that Cul4-Ddb1-DCAF1 E3 ligase complex associated with a DNA damage repair complex including SMC1A and promoted phosphorylation of Smc1a to aid in DNA damage repair (39). As Ddb1 is crucial for activity of Cul4-Ddb1-DCAFs E3 ligase complex, deletion of Ddb1 in effector CD4 + T cells could result in augmented protein levels of substrates involved in regulation of cell cycle, such as Cdt1 (18,19), p21 (20,21), and Cyclin D (40)(41)(42).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, mutations in NER components such as Ddb1 deletion cause aberrant accumulation of DNA damage that lead to activation of the ATM/ATR-Chk1 and p53 pathway and consequently promotes cell cycle arrest and cell death. These findings are consistent with a very recent report that ablation of Cul4b in mature T cells resulted in impaired survival and proliferation accompanied by accumulation of DNA damage upon T-cell stimulation ( 39 ). This recent study further demonstrated that Cul4-Ddb1-DCAF1 E3 ligase complex associated with a DNA damage repair complex including SMC1A and promoted phosphorylation of Smc1a to aid in DNA damage repair ( 39 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Recently, it was shown that neddylated Cul-4b is more abundant after T cell activation, and it is necessary to maintain the survival rate of effector CD4 + T cells. Since Cul-4b lacking CD4 + T cells are not capable of repairing DNA damage, they are more likely to undergo apoptosis ( Dar et al, 2021 ). Taken together, neddylation is an indispensable process for T cells to function properly and survive.…”
Section: Neddylation and Adaptive Immunitymentioning
confidence: 99%
“…This study revealed Cul4B in promoting the repair of damaged DNA to allow survival and expansion of activated T cells. 20 Hung et al found that myeloid-specific Cul4B deficiency worsens LPS-induced peritonitis, and Cul4B deficiency leads to enhanced DNA replication and proliferation, increased production of chemokines, and decreased proinflammatory production cytokines of macrophages. 21 These results suggested that CUL4B played a crucial role in the immune system.…”
Section: Introductionmentioning
confidence: 99%